Pengemis dalam Tinjauan Ekonomi Islam - A. Taufiq Buhari (STAI Syaichona Moh. Cholil Bangkalan, 2015)
Poverty is a complex issue, not only rooted in the diversity ofeconomic viewpoint but as the embodiment of interactions involving almostall aspects of human life. In the Islamic perspective, is deemed valuable workundertaken so far to meet human needs. Islamic economics emphasis on socialjustice. Islam does not only want high growth, but also equity. Ownership ofproperty is the pressure the use of property for something useful, not only forhimself but of others and society as a whole.